Mitigating Engineering Profession Regulatory Gaps - Ndiba, Peter (Academia Kenya, 2021)
Regulation of the engineering profession is critical in developing and safeguarding the nation’s infrastructural systems. The regulation of engineering education through separate legal provisions of both the Commission for University Education (CUE) and Engineering Board of Kenya (EBK) resulted in uncoordinated and sometimes contradicting directives. The attempt by the University (Amendment) Act No. 48 2016, which was upheld by the High Court ruling of 2020, to resolve the duality by vesting the mandate for accreditation of programmes on CUE has created gaps in the regulation of the engineering profession. This policy brief traces regulation of university education in Kenya, identifies the regulatory gaps and suggests mitigation measures.
Keywords: Engineering; Kenya